Vernacular architecture in kabylia and its characteristics in the context of visual restoration of architectural heritage - Faycal Boubenia; Ilvitskaya S.V.; Lobkova T.V. (E3S Web of Conferences, 2023)
This article is a study on Kabylian vernacular architecture in the district of Ammal, Kabylia. In an era marked by an absence of architectural identity, we want to focus on a presentative sense of the architecture of the past, which should remain engraved in memory and which is a cultural wealth of this time. As an object of study, we focus on the analysis of individual houses built from soil and stone and other local materials. The Kabylian vernacular house, which reflects the principles of vernacular architecture, bioclimatic architecture and is part of the fundamentals of sustainable development, represents architectural know-how that should be used in new contemporary architectural projects in the Kabylian region, on the one hand, and on the other, it is an architecture that should be conserved and preserved, given the historical and distinctive role it plays in the rich heritage of Kabylia. The research involves measuring work at the site of the objects, researching and classifying materials, interviewing people in the region and specialists who are interested in history in order to have reliable explanations for the methods used in construction, the different construction processes and justification for the choice of materials. Part of the research is historical and demographic in nature, and relates to the changes that have led to a lack of interest in Kabylian vernacular architecture, and village life in general. The article focuses on illustrating an image of the past that can be reconstructed as an identity for the modern world, that participates in its evolution.